Enhancement of Exciton Emission from Multilayer MoS2 at High Temperatures: Intervalley Transfer versus Interlayer Decoupling - Li, Yuanzheng; Xu, Haiyang; Liu, Weizhen; Yang, Guochun; Shi, Jia; Liu, Zheng; Liu, Xinfeng; Wang, Zhongqiang; Tang, Qingxin; Liu, Yichun (Small (Weinheim an der Bergstrasse, Germany), 2017)
It is very important to obtain a deeper understand of the carrier dynamics for indirect‐bandgap multilayer MoS2 and to make further improvements to the luminescence efficiency. Herein, an anomalous luminescence behavior of multilayer MoS2 is reported, and its exciton emission is significantly enhanced at high temperatures. Temperature‐dependent Raman studies and electronic structure calculations reveal that this experimental observation cannot be fully explained by a common mechanism of thermal‐expansion‐induced interlayer decoupling. Instead, a new model involving the intervalley transfer of thermally activated carriers from Λ/Γ point to K point is proposed to understand the high‐temperature luminescence enhancement of multilayer MoS2. Steady‐state and transient‐state fluorescence measurements show that both the lifetime and intensity of the exciton emission increase relatively to increasing temperature. These two experimental evidences, as well as a calculation of carrier population, provide strong support for the proposed model. For indirect‐bandgap multilayer MoS2 it is very important to further improve the luminescence efficiency and to gain a deeper understanding of the carrier dynamics. Herein, an experimental observation of high‐temperature exciton emission from multilayer MoS2 is reported. Theoretical and experimental studies reveal that a new model involving the intervalley transfer of thermally activated carriers is proposed to well explain this anomalous luminescence behavior.